1988
DOI: 10.1101/gad.2.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Changes in histone gene dosage alter transcription in yeast.

Abstract: Chromatin structure is believed to be important for a number of cellular processes, including transcription. However, the role of nucleosomes in transcription is not well understood. We have identified the yeast histone locus HTB1-HTB1, encoding histones H2A and H2B, as a suppressor of solo 8 insertion mutations that inhibit adjacent gene expression. The HTA1-HTB1 locus causes suppression either when present on a high-copy-number plasmid or when mutant. These changes in HTA1-HTB1 alter transcription of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
202
1
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(212 citation statements)
references
References 45 publications
8
202
1
1
Order By: Relevance
“…After transfer to media containing 5FOA, which selects for cells that have lost the URA3-marked plasmid carrying the wild-type HTA1-HTB1 locus, transformants were screened for recessive phenotypes. As an internal control for the level of mutagenesis, we also screened transformants for sensitivity to 5FOA, which indicates inability to lose the wild-type plasmid and therefore a complete loss-of-function mutation in HTA1, and suppression of the insertion mutation lys2-128␦, which probably indicates partial loss of function (18,31). Of 2,200 transformants tested, 83 were 5FOA resistant and 70 showed an Spt Ϫ phenotype, suggesting that the proportion of transformants carrying hta1 mutations was at least 6%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After transfer to media containing 5FOA, which selects for cells that have lost the URA3-marked plasmid carrying the wild-type HTA1-HTB1 locus, transformants were screened for recessive phenotypes. As an internal control for the level of mutagenesis, we also screened transformants for sensitivity to 5FOA, which indicates inability to lose the wild-type plasmid and therefore a complete loss-of-function mutation in HTA1, and suppression of the insertion mutation lys2-128␦, which probably indicates partial loss of function (18,31). Of 2,200 transformants tested, 83 were 5FOA resistant and 70 showed an Spt Ϫ phenotype, suggesting that the proportion of transformants carrying hta1 mutations was at least 6%.…”
Section: Methodsmentioning
confidence: 99%
“…No transcriptional role has previously been demonstrated for the N-terminal tails of histones H2A and H2B, although the presence of at least one of the two tails is required for viability (63). Also, a reduction of histone H2A-H2B gene dosage can restore transcription to certain inactivated promoters (18,30). These in vivo experiments, then, show that changes in histones can lead to many kinds of transcriptional defects.…”
mentioning
confidence: 99%
“…Many in vivo studies have been performed on the new nature of core histones-in addition to the vital role in chromatin organization mentioned above, especially in yeasts (Hereford et al 1982;Meeks-Wagner & Hartwell 1986;Norris & Osley 1987;Osley & Lycan 1987;Clark-Adams et al 1988;Norris et al 1988;Grunstein 1990;Carr et al 1994;Hirschhorn et al 1995)because gene replacement experiments on them can be carried out easily. Moreover, it has been reported that in Saccharomyces cerevisiae, the deletion of H4 N-terminal residues 4-23 or mutagenesis of the acetylatable lysines in this region decreases the activation of the GAL1 promoter, while the deletion of N-terminal residues 4-15 of H3 or the mutagenesis of the acetylatable lysines causes a hyperactivation of GAL1 (Fisher-Adams & Grunstein 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The SPT genes encode many proteins important in transcription, including subunits of the SAGA histone-modifying complex (Grant et al 1998), TBP itself, and histones (Clark-Adams et al 1988;Winston and Sudarsanam 1998;Yamaguchi et al 2001). SPT10 is not an essential gene, but the null allele is associated with very slow growth and defects in gene regulation (Denis and Malvar 1990;Natsoulis et al 1991;Prelich and Winston 1993;Yamashita 1993;Dollard et al 1994;Natsoulis et al 1994).…”
Section: Cell-cycle-dependent Activation Of the Histone Genesmentioning
confidence: 99%